CONTESTATION OF #FOODESTATE DISCOURSE AS A SOLUTION TO THE THREAT OF JOKOWI'S ERA FOOD CRISIS ON TWITTER SOCIAL MEDIA - Febrian Nugroho; Edi Santoso; Nana Sutikna (Jurnal Scientia, 2023)
The food estate is considered a solution to the food crisis. It was a priority program for three Indonesian regimes: Suharto, Susilo Bambang Yudhoyono, and Joko Widodo. Today's, public attention is still focused on #foodestate issues. Furthermore, the modern era facilitates the public expression of responses through social media. This research aims to analyze netizen conversations on Twitter regarding Jokowi's policy concerning food estates. The method used in this research is communication network analysis (CNA), with data collected from Netlytic through crawling #foodestate issues on Twitter during 2020—2022. Measurement focuses on the most frequently discussed, actor-dominating, network-structured communication and netizen responses. The conclusion of this research dominated negative sentiment responses that showed public dissatisfaction, actor dominance, which represents government concern, and the lowest level of public involvement in discussing #foodestate issues. This research provides information to the government as a recommendation to improve food estate programs to solve the food crisis threat.